(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The essence of health care is to preserve the health of students with the help of pedagogical tools, forms, methods and techniques. The teacher’s task is to help students acquire knowledge, skills and abilities to preserve their own health and to form their health care competencies, which are among the key ones for the Ukrainian education system. The essence of health care is to preserve the health of students with the help of pedagogical tools, forms, methods and techniques. The leading motive of health care is the message: through pedagogy - to health, through education - to a healthy lifestyle. Accordingly, the purpose of health care is to create conditions and carry out activities aimed at preserving the health of students. The concept of the New Ukrainian School is built on the priorities of educating a competent personality of a child who possesses knowledge, knows how to apply it in everyday life, adapt to the realities of today, overcome life’s difficulties, take care of health and maintain it at an appropriate level, knows how to counteract negative external influences. Teaching children to protect and strengthen their health is the most important task of the New Ukrainian School. The basic requirement for conducting the educational process in primary school is to follow the principles of health care, to use health care educational technologies. The task of the health care pedagogy is to provide students with the knowledge about a healthy lifestyle, to form a culture of health for the future independent life, the ability to take care of their own health and to treat the health of other people with care. The main professional task of a primary school teacher today is to ensure comfortable and safe conditions for the educational process, taking into account the age and individual characteristics of students of primary school age, the use of health care learning technologies, the implementation of pedagogical and ergonomic requirements into the work of primary school.